2014
DOI: 10.1590/s1415-47572014000100018
|View full text |Cite
|
Sign up to set email alerts
|

Use of the heteroduplex mobility assay and cell sorting to select genome sequences of the CCR5 gene in HEK 293T cells edited by transcription activator-like effector nucleases

Abstract: Engineered nucleases such as zinc finger nucleases (ZFN) and transcription activator-like effector nucleases (TALEN) are one of the most promising tools for modifying genomes. These site-specific enzymes cause double-strand breaks that allow gene disruption or gene insertion, thereby facilitating genetic manipulation. The major problem associated with this approach is the labor-intensive procedures required to screen and confirm the cellular modification by nucleases. In this work, we produced a TALEN that tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…However, these strategies do not silence CCR5 expression permanently. To reach this goal, some gene editing technologies, including zinc finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs), have been used to knock out the CCR5 gene [ 56 , 57 ]. Several clinical trials using autologous infusions of CCR5 -modified CD4 + T cells are currently under way.…”
Section: Full or Partial Replacement Of The Immune System Through Genmentioning
confidence: 99%
“…However, these strategies do not silence CCR5 expression permanently. To reach this goal, some gene editing technologies, including zinc finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs), have been used to knock out the CCR5 gene [ 56 , 57 ]. Several clinical trials using autologous infusions of CCR5 -modified CD4 + T cells are currently under way.…”
Section: Full or Partial Replacement Of The Immune System Through Genmentioning
confidence: 99%
“…Fluorescence measurements by flow cytometry showed that GFP + cells were most abundant in CRISPR-Cas9-transfected cells 48 h after transfection ( Figure 3 ). Whereas Miller’s TALEN transfections resulted in ~10% of RFP + /GFP + cells ( Nerys-Junior et al , 2014 ), CRISPR-Cas9 transfections resulted in 57.2% of GFP + cells ( Figure 3 ). The transfections were repeated 10 times in the same conditions and in all cases the proportion of gated cells showed no more than 2% variability.…”
Section: Resultsmentioning
confidence: 99%
“…This same approach was previously used to show that the interval with the highest proportion of RFP + /GFP + cells in TALEN+pRGS-CR transfections was 72 h after transfection ( Kim et al. , 2011 ; Nerys-Junior et al , 2014 ) and this interval was used in cell sorting of TALEN+pRGS-CR transfections. For CRISPR-Cas9-transfected HEK293T cells, the best interval (highest proportion of GFP + cells) was 48 h post-transfection.…”
Section: Methodsmentioning
confidence: 99%
“…To detect designer nuclease induced in/del mutations, T7E1 assays or HMA 12 , 24 , 25 based on HD formation of mutated and unmutated DNA are widely used. HD based assays work independent of the size of in/dels and there is no need for special equipment.…”
Section: Discussionmentioning
confidence: 99%